Adipose-Derived Stem Cells Exosomes Improve Fat Graft Survival by Promoting Prolipogenetic Abilities through Wnt/β-Catenin Pathway. (6th May 2022) - Chen, Kexin; Xiong, Jiachao; Xu, Sha; Wu, Minliang; Xue, Chunyu; Wu, Minjuan; Lv, Chuan; Wang, Yuchong
Abstract : Autologous fat grafting has been widely used in plastic surgery in recent years, but the unstable retention of fat graft has always been a key clinical problem. Adipose tissue has poor tolerant to ischemia, so the transplanted adipose tissue needs to rebuild blood supply at an early stage in order to survive stably. Our previous study has found that comparing to human foreskin fibroblast exosome (HFF-Exo), human adipose-derived stem cells exosome (hADSC-Exo) can significantly improve the proliferation of vascular endothelial cells and the angiogenic effect of artificial dermal preconstructed flaps. Therefore, the ability of hADSC-Exo to improve the retention of adipose grafts and its potential regenerative mechanism aroused our strong interest. In this study, we applied hADSC-Exo and HFF-Exo to adipose grafts and explored the potential regeneration mechanism through various means such as bioinformatics, immunofluorescence, immunohistochemistry, and adipogenic differentiation. The results showed that hADSC-Exo can significantly promote grafts angiogenesis and adipogenic differentiation of ADSC to improve the retention of fat grafts and may downregulate the Wnt/ β -catenin signaling pathway to promote the adipogenic differentiation. In summary, our results provide a theoretical basis for the clinical translation of hADSC-Exo in fat grafting.